Hyperoxia-induced lens damage in rabbit: protective effects of N-acetylcysteine - Wang, Ping (Molecular Vision, 2009)
PURPOSE: To investigate the efficacies of different concentrations of N-acetylcysteine (NAC) in preventing hyperoxia-induced lens opacification and changes to biochemical parameters in organ-cultured rabbit lenses. METHODS: Thirty-six lenses from adult rabbits were divided into the control group (group A), the hyperoxia-exposed group (group B), and the hyperoxia-exposed, NAC-treated groups: 5 mM NAC (group C), 10 mM NAC (group D), 20 mM NAC (group E), and 40 mM NAC (group F). Groups B–F were incubated with hyperoxia (pO(2)>80%) for 4 h per day for 7 d. Lens transparency, histology, and enzymatic activities were measured after incubation. RESULTS: Gross examination of these lenses revealed some severe cortical opacification in group B, and moderate cortical opacification in the lenses of groups C and D. There was minimal cortical opacification in groups A, E, and F. The activities of Na, K-ATPase, and catalase were significantly (p<0.05) lower in group B (38.2%) than in group A (39.9%). It was also lower in group E and F lenses (p<0.05), which had higher levels of NAC-protected enzymes. The glutathione and water-soluble protein content were significantly lower in group B lenses than in group A, E, or F lenses (p<0.05). However, there was no difference between group E and F lenses (p>0.05). CONCLUSIONS: The present data suggests that NAC (20 mM–40 mM) significantly prevented experimental lenses’ hyperoxia-induced cortical opacification, indicating NAC’s potential role in protecting lenses against cataracts induced by high oxygen levels.